Supplier Entry Barriers to Global Value Chains for Clothing: The Roles of Business-state Relations in Vietnam and of Lead Firm Strategies in Europe - Lotte Thomsen (University of Copenhagen, 2006)
In recent decades, exports of clothing have been one of the most dynamic segments of world trade. Together with textiles, the clothing industry was the first manufacturing industry to acquire a global dimension, and gradually it has become highly dispersed geo-graphically across both developed and developing countries (Dicken, 1998). Amongst other things, this has derived from the industry's search for cheap labour, not least in developing countries, and also from the quota system institutionalised by the Multi-fibre Arrangement (MFA) and the Agreement on Textiles and Clothing (ATC) that successively regulated the clothing trade between 1974 and 20051. These agreements limited the export opportunities for producers, and production activities were therefore often shifted to locations with fewer restrictions or preferential market access.
hdl:10398/9479
Keywords: 650